We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
209
1
avatar

Find $$\sum_{k = 0}^{10} (k + 2) \cdot 3 \cdot 2^k.$$\(Find $$\sum_{k = 0}^{10} (k + 2) \cdot 3 \cdot 2^k.$$\)

 Mar 20, 2018
 #1
avatar+22192 
0

Find $$\sum_{k = 0}^{10} (k + 2) \cdot 3 \cdot 2^k.$$

 

\(\displaystyle \sum \limits_{k = 0}^{10} (k + 2) \cdot 3 \cdot 2^k = 33 \cdot 2^{11} = 67584\)

 

laugh

 Mar 20, 2018

5 Online Users